Role of habitat complexity and predation in the structuring of aquatic communities - Soukup, Pavel (Jihočeská univerzita, 2022)
This thesis focuses on the roles habitat complexity and predation play in the structuring of aquatic communities. Chapter one provides an overview of the way habitat complexity structures communities separately, and by altering predator prey interactions in all aquatic habitats. The following two chapters examine their combined effects using different predator-prey pairs and time scopes: short-term laboratory experiments and a medium-term mesocosm experiment.
Role of habitat complexity and predation in the structuring of aquatic communities
Keywords: struktura prostředí; predace; utváření společenstev; habitat complexity; predation; community assembly